BANTUAN REKONSILIASI DATA TRIAL BALANCE AWAL DAN PELATIHAN INPUT DAN EXPORT TRIAL BALANCE AWAL DI SOFTWARE AKUNTANSI BAGI KARYAWAN MGG - Kristian, Michelle; Velinda; Kevin; Bong Su Yan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The Faculty of Economics and Business team held community service activities carried out by the team in the Odd semester 2024/2025 focusing on financial reporting problems faced by MGG. Partners' financial reports are not integrated between divisions and between years, so manual corrections are often made. The aim of the PKM activity is to provide assistance in initial trial balance data reconciliation and initial trial balance input and export training in accounting software for employees in accordance with the Statement of Financial Accounting Standards (PSAK). Based on the problems and situation analysis, an integrated computerized accounting system is needed. well and TB data for July 2024 with ending June 2024, and Partners also need Initial Trial Balance input and export training in Accounting Software. PKM activities aim to provide assistance in reconciling Initial Trial Balanced data and provide training for partner employees regarding the input and export process on Initial Trial Balance data in accounting software. Community service activities have the aim that after the training process, input process, data export process from manual (Excel) to accounting software, the Accounting department can create financial reports according to (PSAK) accurately and data integrity can be fulfilled. The discussion of PKM Reconciliation Assistance has two sessions, the first session: Assistance for Reconciling Initial Trial Balance Data, and the second session discusses how to train in inputting data for July and exporting Initial Trial Balance data for June 2024, in Accounting Software. The result of the PKM method is financial statement meet deadline and accuratel, with support from PKM activities, increasing efficiency in accounting system-based data processing. ABSTRAK Kegiatan pengabdian masyarakat pada semester ganjil 2024/2025 yang dilakukan tim Fakultas Ekonomi dan Bisnis Universitas Tarumanagara berfokus pada masalah pelaporan keuangan yang dihadapi MGG. Laporan keuangan mitra tidak terintegrasi antardivisi dan antartahun sehingga sering dilakukan koreksi manual. Adapun tujuan kegiatan PKM adalah untuk memberikan bantuan rekonsilisi data trial balance awal dan pelatihan input dan export trial balance awal di software akuntansi bagi karyawan mengikuti Pernyataan Standar Akuntansi Keuangan (PSAK), Dari permasalahan dan analisis situasi, mitra memerlukan sistem akuntansi yang terintegrasi dan data TB Juli 2024 dengan ending Juni 2024, dan mitra juga memerlukan pelatihan input dan export trial balance awal di software akuntansi. Kegiatan PKM bertujuan untuk memberikan bantuan dalam rekonsiliasi data balanced trial awal dan memberikan training bagi karyawan mitra tentang proses penginputan dan export atas data trial balance awal di software akuntansi. Kegiatan pengabdian kepada masyarakat mempunyai tujuan yaitu setelah proses pelatihan, proses input, proses ekspor data dari manual (excel) ke software akuntansi, maka bagian akuntansi bisa membuat laporan keuangan sesuai PSAK secara akurat dan integritas data dapat terpenuhi. Pembahasan PKM bantuan rekonsiliasi dibagi menjadi dua sesi: sesi pertama membahas bantuan rekonsiliasi data trial balance awal, dan sesi kedua membahas bagaimana pelatihan input data bulan Juli dan export trial balance awal data bulan juni 2024, di software akuntansi. Hasil dari metode PKM adalah upaya untuk bekerja memenuhi tenggat waktu dan akurat, dengan support dari kegiatan PKM meningkatkan efisiensi dalam proses pengolahan data berbasis sistem akuntansi.